2023
DOI: 10.1186/s12943-023-01845-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the anti-PD-1/PD-L1 era: promising role of the BTLA/HVEM axis as a future target for cancer immunotherapy

Christian Sordo-Bahamonde,
Seila Lorenzo-Herrero,
Rocío Granda-Díaz
et al.

Abstract: Recent introduction of monoclonal antibodies targeting immune checkpoints to harness antitumor immunity has revolutionized the cancer treatment landscape. The therapeutic success of immune checkpoint blockade (ICB)-based therapies mainly relies on PD-1/PD-L1 and CTLA-4 blockade. However, the limited overall responses and lack of reliable predictive biomarkers of patient´s response are major pitfalls limiting immunotherapy success. Hence, this reflects the compelling need of unveiling novel targets for immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 128 publications
(179 reference statements)
0
15
0
Order By: Relevance
“…Our analysis suggests that excluding any of the studies did not have a major impact on the OS HR. Specifically, the HR estimates for OS ranged from 1.810 (95% CI: 1.464-2.239) when excluding Zeng et al., 2021 ( 2 ) to 2.003 (95% CI: 1.585-2.531) when excluding Sooi et al., ( 18 ) ( Figure 5A ). In addition, the sensitivity analysis indicated that the removal of any one study did not have a major impact on the overall results of PFS.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our analysis suggests that excluding any of the studies did not have a major impact on the OS HR. Specifically, the HR estimates for OS ranged from 1.810 (95% CI: 1.464-2.239) when excluding Zeng et al., 2021 ( 2 ) to 2.003 (95% CI: 1.585-2.531) when excluding Sooi et al., ( 18 ) ( Figure 5A ). In addition, the sensitivity analysis indicated that the removal of any one study did not have a major impact on the overall results of PFS.…”
Section: Resultsmentioning
confidence: 98%
“…Cancer, being the primary cause of mortality, constitutes a substantial menace to global public health as its burden continues to escalate ( 1 ). The recent emergence of monoclonal antibodies targeting immune checkpoints has fundamentally transformed the field of cancer therapy ( 2 , 3 ). The success of treatment based on immune checkpoint blockade (ICB) largely relies on blocking PD-1/PD-L1 and CTLA-4 ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…HVEM is implicated in various immune regulatory processes, including promoting Treg differentiation, inhibiting antigen processing, and presenting major histocompatibility complexes I (MHC I) molecules and αβT. Furthermore, the expression of PD-1, CTLA-4, TIM-3, V-domain Ig suppressor of T cell activation (VISTA), and lymphocyte activating 3 (LAG3) positively correlates with HVEM, suggesting its potential role in immune suppression within the GBM microenvironment [ 94 , 95 ]. High levels of lysosomal-associated membrane protein 2A (LAMP2A) in GBM and the TME are associated with temozolomide (TMZ) resistance and tumor progression.…”
Section: The Immune Regulation In Glioblastomamentioning
confidence: 99%
“…Like PD-1, BTLA negatively regulates T cell activation. Despite both BTLA and PD-1 possessing ITSM and ITIM motifs, PD-1 predominantly relies on ITSM to achieve its inhibitory function, whereas BTLA necessitates the concurrent presence of both ITIM and ITSM [ 56 ]. Resting γδ T cells, especially naïve γδ T cells, express high levels of BTLA, which is downregulated in the T CM and T EM stages.…”
Section: The Correlation Between the Pd-1/pd-l1 Axis And The Immunosu...mentioning
confidence: 99%